Determinants of Carbon Emission and Rebound Effect in Asean Countries: Kaya and LMDI Decomposition - Sudarmaji, Eka; Achsani, Noer Azam; Arkeman, Yandra; Fahmi, Idqan (Indonesian Journal of Business and Entrepreneurship, 2022)
All ASEAN countries have achieved extraordinarily high growth rates in their history of economic development. They relied on new energy efficiency technologies to reduce their energy intensity while avoiding the rebound effect. Academics debate told that the rebound effect happened due to the false policies. Hence, the other strategy to stimulate increased energy efficiency in the economic sector is essential for government policy in overcoming resource constraints. This study used the logarithmic-mean Divisia index (LMDI) decomposition and KAYA identity to recognize the determinant factors of carbon emissions and rebound effect changes in ASEAN countries. This study also analyzed the factors behind the shift in ASEAN's carbon emissions and identified the differences between ASEAN member countries. The carbon emissions are decomposed into the population, GDP growth, energy intensity, and carbon intensity. One of the purposes of this paper advocated enhancing efficiency, notably in the energy efficiency sector's plan to encourage government measures. According to the research findings, substantial energy rebounds in Indonesia have revealed that energy efficiency gains in Indonesia may be related to the rebound effect. Indonesia sought to go in this direction, with the national energy policy aiming to lower energy efficiency by 1% each year to stimulate energy savings in all sectors.Keywords: ASEAN, energy efficiency, kaya index, LMDI, rebound effect